KOMPOSISI KIMIA BATANG PANDAN MENGKUANG (Pandanus atrocarpus Griff) SEBAGAI BAHAN BAKU ALTERNATIF PULP (Chemical Composition of Mengkuang Pandanus (Pandanus Artocarpus Griff) As Pulp Alternative Raw Material) - Yeni Mariani (Universitas Tanjungpura, 2011)
A fundamental study was carried out to explore the properties of pandan mengkuang stem (Pandanus atrocarpus Griff). In this study chemical compound was investigated, with regards to pulp and paper production. Completely randomized design was used and as a factor was plant age. The result showed that the level of plant age, had significantly affected to the content of holocellulose, ?-cellulose, pentosan and 1% NaOH solubility. The percentage of extractive content, lignin, holocellulose, ?-cellulose, pentosan, ash content and 1% NaOH solubility were 2.83% 3.71 %; 23.08% 23.88%; 66.8% 68.21%; 38.08% 39.06%; 20.68% 21.14%; 2.7% 3.18%; 24.47% 27.19% respectively. The overall results showed that pandan mengkuang has a promising potential to be used in pulp and paper production. Keyword : chemical properties, pandan mengkuang, Pandanus atrocarpus, pulp, nonwood.